Polysialic Acid Acute Depletion Induces Structural Plasticity in Interneurons and Impairs the Excitation/Inhibition Balance in Medial Prefrontal Cortex Organotypic Cultures - Castillo-Gómez, Esther; Pérez-Rando, Marta; Vidueira, Sandra; Nacher, Juan (Frontiers in Cellular Neuroscience, 2016)
The structure and function of the medial prefrontal cortex (mPFC) is affected in several neuropsychiatric disorders, including schizophrenia and major depression. Recent studies suggest that imbalances between excitatory and inhibitory activity (E/I) may be responsible for this cortical dysfunction and, therefore, may underlie the core symptoms of these diseases. This E/I imbalance seems to be correlated with alterations in the plasticity of interneurons but there is still scarce information on the mechanisms that may link these phenomena. The polysialylated form of the neural cell adhesion molecule (PSA-NCAM) is a good candidate, because it modulates the neuronal plasticity of interneurons and its expression is altered in schizophrenia and major depression. To address this question, we have developed an in vitro model using mPFC organotypic cultures of transgenic mice displaying fluorescent spiny interneurons. After enzymatic depletion of PSA, the spine density of interneurons, the number of synaptic puncta surrounding pyramidal neuron somata and the E/I ratio were strongly affected. These results point to the polysialylation of NCAM as an important factor in the maintenance of E/I balance and the structural plasticity of interneurons. This may be particularly relevant for better understanding the etiology of schizophrenia and major depression.